Persepsi Akademisi, Praktisi, dan Mahasiswa Akuntansi Terhadap Keahlian Akuntan Forensik di Makassar - Sri Rahayu Husen (Lembaga Penelitian & Pengabdian pada Masyarakat (LPPM) Universitas Mikroskil, 2017)
Perception of Academics, Practitioners, and Accounting Students In Forensic Accounting Expertise In Makassar. This study aimed to analyze the differences of perceptual academics, practitioners, and accounting students about forensic accounting in the accounting expertise in Makassar, using differences test analysis in the processing of the data using SPSS software, using primary data from elements of Academics, Practitioners, and Accounting Students in Makassar. Sample with a probability sample study techniques Stages Two Radom Sampling Stratified Sampling. The total sample of 150 people. Results of this study indicate that there arde not differences about perceiption among academician, practitioners, and accounting students of about forensic accounting expertise in Makassar .